The Effects of Aging Time on the Eating Quality of Gluteus Medius Steaks - Chesney A. Effling; Lauren M. Frink; Stephanie L. Witberler; Mason J. Prester; Jerrad F. Legako; Dale R. Woerner; Rhonda K. Miller; Chris R. Kerth; Mahesh N. Nair; Jessica M. Lancaster; Travis G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this study was to determine the palatability characteristics and color traits of gluteus medius steaks aged 14, 28, 35, 42, 49, 56, 63, and 70 days. Study Description: Beef top sirloin butt subprimals were assigned to one of eight aging periods. Once aged, the gluteus medius was fabricated into 1-in. steaks. Steaks were used for consumer panels, Warner-Bratzler Shear Force (WBSF), or raw/cooked color evaluation. Color data were collected on raw steaks. Steaks were cooked to 160°F and internal color data measured. Samples were cooled for 24 hours before WBSF determination. Steaks were cooked to 160°F for consumer ratings on overall juiciness, tenderness, and flavor liking. Results: Consumers found no difference (P > 0.05) among aging treatments for juiciness, tenderness, flavor, or overall liking. Although there were no differences (P > 0.05) in the percentage of samples rated acceptable for juiciness, tenderness, flavor, or overall liking, all treatments had, at minimum, 83% of samples rated overall acceptable by the consumers. Additionally, there were no differences (P > 0.05) in cooking loss, cooked L* (lightness), a* (redness), b* (yellowness), deoxymyoglobin (DMb), oxymyoglobin (OMb), metmyoglobin (MMb), chroma, or hue angle among all treatments. Steaks that were aged for 14 days had a higher (P < 0.05) WBSF value than all other treatments. Steaks aged for 63 and 70 days were more tender (P < 0.05) than samples aged for 42 days or less. Although there were differences found in raw color, there were few evident trends. Steaks that were aged for 14, 49, and 56 days were redder (P < 0.05) than those aged for 63 and 70 days. Steaks aged for 14 days were darker (P < 0.05) than steaks aged for 49 days or more. Although there were no differences (P > 0.05) in raw calculated MMb, there were differences (P < 0.05) in DMb, with values being higher in steaks aged 14, 35, 49, and 56 days than at 63 and 70 days. Furthermore, OMb was higher (P < 0.05) at 63 days than at 14, 35, 42, and 56 days. The Bottom Line: These results indicate that extending the aging time of gluteus medius steaks has limited impact on the palatability and color characteristics of the steaks.
Keywords: beef; aging; gluteus medius